2019
DOI: 10.24815/jks.v19i2.18063
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Sex, Age, Nutritional Status and Diabetes Mellitus With Clinical Symptoms MDR Pulmonary Tb at Rsud DR Soetomo

Abstract: Abstract. Multi-drug resistance is a condition where drugs rifampicin and isoniazid is not effective in killing bacteria Mycobacterium tuberculosis. Some of the causes of resistance to OAT are the use of a single drug in the treatment of tuberculosis, the use of drugs is inadequate and the irregular drug administration. In RSUD Dr. Soetomo, 25% of MDR Pulmonary TB patients do not want to be treated because symptoms are mild, no pain and feel the treatment is not comparable with the symptoms. This research is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…7,9 Our study also found that 58.3% of RR TB patients were malnourished (Table 2), which was higher than the results of a study conducted at Dr. Soetomo, which revealed that 51.5% of RR TB patients were malnourished. 18 These findings showed that in South Kalimantan, specifically in Ulin Hospital, poor nutritional status is still a challenge in managing tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Our study also found that 58.3% of RR TB patients were malnourished (Table 2), which was higher than the results of a study conducted at Dr. Soetomo, which revealed that 51.5% of RR TB patients were malnourished. 18 These findings showed that in South Kalimantan, specifically in Ulin Hospital, poor nutritional status is still a challenge in managing tuberculosis.…”
Section: Discussionmentioning
confidence: 99%